Development and characterization of lithium ion solid composite electrolytes prepared by sol gel / Hafizul Mat - Mat, Hafizul (2017)
Solid Composite Electrolytes (SCE) was developed, with LiC104 and LiNCb as the host material in composition with metal oxide, Si d to enhance the conductivity and the lithium transference number. SCE were sintered at 200 °C by using simple sol-gel method to remove the excess water with help of acetic acid as a binder between the interphase of host matrices and the metal oxide. SCE was then tested by using X-Ray Diffractogram (XRD), Field Emission Scanning Electron Microscope (FESEM) and Electrical Impedance Spectroscopy (EIS) to observe the physical properties of SCE in room temperature and also in high temperature. The highest conductivity of SCE is by using LiN03 as host matrix and SiCte as metal oxide which is 9.74 x 10"4 S/cm at room temperature with lower activation energy at higher temperature. Compared to LiC104- Si02, the conductivity of SCE is seemed too low compare with LiN03-Si02 but higher in lithium ion number which is 0.58. Existence of new lattice in XRD diffractogram caused the decrease in ion mobile and caused the ion mobile is anion. The enhancement of conductivity of the SCEs is depended on the amorphous phase of the samples that will create the ion pathways and increase the lithium ion number